Correlation Between Different Follicle Size and their Oocyte Competency in Stimulated Cycles of IVF / ICSI - A - Sravanthi, Havila; Sharma, Nidhi; Chakrabarti, Sudakshina (International Journal of Psychosocial Rehabilitation, 2020)
Abstract:Assisted reproduction involves stimulation of ovaries which causes growth of multiple follicles instead of selection of single dominant follicle in natural cycle. As the cohort of the follicles to be recruited were predestined in the previous cycle, different follicle cohorts grow at different growth rates. The administration of triptorelin (decapeptyl) injection, to trigger luteinizing hormone (LH) surge, is the final step for follicular maturation. This study observes the maturation of oocyte, its association with fertilization rate, and quality of embryos originating from different follicle sizes at the time of recruitment. This study was conducted in 30 infertile women who underwent ICSI and 663 oocytes were retrieved in total. In this study it was observed that quality of embryos improved with larger follicle sizes at the time of retrieval. The ideal size of the follicle at the time of trigger if more than 20mm it was favourable. Oocyte maturation rate which is characterised by conversion into Metaphase II ranged from 7.7 % in follicles 20mm group. It was also observed that 75.8 % of oocytes retrieved from large follicles were fertilised compared to 52.3 % of oocytes were fertillised which were retrieved from 15-19mm follicle size group. This shows that the size of the dominant follicle is linked with the oocyte quality. It was also observed that a small follicular group